2020
DOI: 10.1021/acscentsci.0c00791
|View full text |Cite
|
Sign up to set email alerts
|

Pairing Bacteroides vulgatus LPS Structure with Its Immunomodulatory Effects on Human Cellular Models

Abstract: The gut microbiota guide the development of the host immune system by setting a systemic threshold for immune activation. Lipopolysaccharides (LPSs) from gut bacteria are able to trigger systemic and local proinflammatory and immunomodulatory responses, and this capability strongly relies on their fine structures. Up to now, only a few LPS structures from gut commensals have been elucidated; therefore, the molecular motifs that may be important for LPS–mammalian cell interactions at the gut level are still obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 57 publications
(140 reference statements)
4
74
0
Order By: Relevance
“…ET-B showed high fatty acid metabolism and LPS production ( Figure 4 ), a common endotoxin in the human body. LPS produced by intestinal bacteria can trigger systemic and local pro-inflammatory and immunomodulatory responses [ 55 ]. In the research of the intestinal type of diabetic patients, it also has concluded that ET-B has more LPS and TNF-α content [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…ET-B showed high fatty acid metabolism and LPS production ( Figure 4 ), a common endotoxin in the human body. LPS produced by intestinal bacteria can trigger systemic and local pro-inflammatory and immunomodulatory responses [ 55 ]. In the research of the intestinal type of diabetic patients, it also has concluded that ET-B has more LPS and TNF-α content [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the administration of Bacteroides LPS re-established intestinal immune homeostasis in a mouse model for experimental colitis, thus correlating the health-promoting effects to the weak agoniztic properties of this LPS 24,25 . Further, in the human innate immune system, we demonstrated a relevant capability of the LPS to induce antiinflammatory cytokines 26 . The O-antigen of B. vulgatus mpk LPS consists of a disaccharide repeating unit of 27 (Fig.…”
mentioning
confidence: 84%
“…1 × 10 6 BMDCs/ml were stimulated with PBS (mock, Thermo Fisher Scientific), B. vulgatus or E. coli at a multiplicity of infection (MOI) of 1 at 37°C. 100 ng/ml isolated LPS of B. vulgatus [LPS BV , isolated as described in ( 26 , 27 ) and ( 28 )] or E. coli [LPS EC , isolated as described in ( 26 , 27 ) and ( 28 )] were used for stimulation. For stimulation with a complex microbiota, fecal samples were collected from SPF Rag1 -/- mice prior to administration of bacteria and induction of colitis, as well as at the end of the experiment (see T cell transfer in Rag1 -/- mice).…”
Section: Methodsmentioning
confidence: 99%